2018
DOI: 10.1002/jcp.26529
|View full text |Cite
|
Sign up to set email alerts
|

RRM2 promotes the progression of human glioblastoma

Abstract: Glioblastoma pathogenesis is related to multiple processes that affected by dozens of regulatory factors, but the potential underlying factors regulating glioblastoma progression remains unclear. The goal of this research was to determine how the ribonucleotide reductase M2 subunit (RRM2) influenced proliferation, invasion, migration, and apoptosis of human glioblastoma cells. The level of proliferation of human glioblastoma cells was measured through CCK8, colony formation assay and immunofluorescence stains.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 24 publications
3
42
0
Order By: Relevance
“…The high level of RRM2 expression has received extensive attention in several cancers (38). It has been proven that the overexpression of RRM2 can promote the proliferation, migration and invasion of GBM cells and inhibit apoptosis in cell experiments (39). The same results were observed in animal experiments, which may explain its influence on OS.…”
Section: Discussionmentioning
confidence: 75%
“…The high level of RRM2 expression has received extensive attention in several cancers (38). It has been proven that the overexpression of RRM2 can promote the proliferation, migration and invasion of GBM cells and inhibit apoptosis in cell experiments (39). The same results were observed in animal experiments, which may explain its influence on OS.…”
Section: Discussionmentioning
confidence: 75%
“…A recent study indicated that RRM2 upregulation occurred in multiple myeloma tumors and that RRM2 knockdown inhibited multiple myeloma cell proliferation 12 . Li et al illustrated that RRM2 was overexpressed in human glioblastoma cells, and promoted proliferation, migration, and invasion of human glioblastoma cells 34 . Suppression of RRM2 inhibits cell proliferation, causes cell cycle arrest, and promotes the apoptosis of human neuroblastoma cells 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Another example was RRM2 and BRIP1, which was significantly correlated with each other in expression ( Figure 6C, R = 0.93 and p-value < 0.001). RRM2 had been found to promote the progression of human GBM and was a potential prognostic biomarker in glioma (Li et al, 2018a;Sun et al, 2019). BRIP1 was found to be an independent signature, which was correlated with worse prognosis in glioma (de Sousa et al, 2017).…”
Section: Rna-binding Protein Regulatory Network During Glioma Progresmentioning
confidence: 93%